Peran Media Digital dalam Meningkatkan Keterampilan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Abdullah Abdullah; Dwi Wahyudiati; Nurul Lailatul Khusniah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
This study aims to examine the role of digital media in improving students' learning skills in Islamic Religious Education (PAI). The method used is a qualitative approach with a library research type, namely by reviewing various library sources such as books, scientific journals, and other relevant publications. The results of the study indicate that digital media has a significant contribution to improving students' learning skills, including critical thinking skills, conceptual understanding, creativity, and independence in learning. The use of digital media such as learning videos, educational applications, and e-learning platforms can provide a more interactive, interesting, and flexible learning process. However, the success of digital media utilization is also influenced by several factors, including teacher readiness, the availability of supporting facilities, and the level of digital literacy of students. Therefore, the right strategy is needed in integrating digital media into learning activities to obtain maximum results.